2002
DOI: 10.1292/jvms.64.489
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Promoting Effect of Phenolphthalein on Development of Lung Tumors Induced by N-ethyl-N-nitrosourea in Transgenic Mice Carrying Human Prototype c-Ha-ras Gene.

Abstract: ABSTRACT. In order to examine tumor modifying effects of phenolphthalein (PhP), female transgenic mice carrying human prototype cHa-ras gene (rasH2 mice) were given a single intraperitoneal injection of 60 mg/kg body weight of N-ethyl-N-nitrosourea (ENU), followed by the diet containing 12,000 ppm PhP for 26-week. Histopathologically, alveolar hyperplasias, adenomas and adenocarcinomas were observed in the ENU + PhP group, but only hyperplasias and adenomas were observed in the ENU alone group. The incidence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…( 10 ) As this transgene is under the control of its own promoter region, it is expressed in the whole body, allowing the study of carcinogenesis in different organs. ( 11 ) RasH2 mice are highly susceptible to chemical carcinogenesis, ( 12–15 ) and currently being evaluated to characterize their biological features by worldwide validation studies with a variety of chemicals. ( 16–18 ) Mutational analysis of endogenous and transgenic c‐Ha‐ ras genes shows that point mutations of the transgene at codons 12 and 61 have been implicated in the development of spontaneous tumors such as lung adenocarcinoma, ( 9,19 ) skin and forestomach squamous cell carcinoma, ( 19,20 ) skin papillomas, ( 9 ) liver ( 21 ) and splenic ( 9 ) hemangiosarcomas, and of chemically induced tumors.…”
mentioning
confidence: 99%
“…( 10 ) As this transgene is under the control of its own promoter region, it is expressed in the whole body, allowing the study of carcinogenesis in different organs. ( 11 ) RasH2 mice are highly susceptible to chemical carcinogenesis, ( 12–15 ) and currently being evaluated to characterize their biological features by worldwide validation studies with a variety of chemicals. ( 16–18 ) Mutational analysis of endogenous and transgenic c‐Ha‐ ras genes shows that point mutations of the transgene at codons 12 and 61 have been implicated in the development of spontaneous tumors such as lung adenocarcinoma, ( 9,19 ) skin and forestomach squamous cell carcinoma, ( 19,20 ) skin papillomas, ( 9 ) liver ( 21 ) and splenic ( 9 ) hemangiosarcomas, and of chemically induced tumors.…”
mentioning
confidence: 99%
“…In einem entsprechenden Versuch war ein Ergebnis bereits nach sechs Monaten zu erhalten -bei Kontrolltieren erst nach zwei Jahren, einem Alter, zu dem die Lebensspanne einer Maus zu Ende geht, und somit viele Tiere nicht mehr für eine statistische Analyse des Experimentes genutzt werden können. Mit Hilfe dieser transgenen Tiere kann also bei entsprechender Fragestellung wesentlich schneller und mit wesentlich weniger Tieren eine statistisch signifikante Aussage erreicht werden (Imaoka et al 2002.…”
Section: Testsystemeunclassified
“…RasH2 mice carry the human c‐Ha‐ ras protooncogene with its own promoter region, ( 9 ) and are highly susceptible to chemical carcinogenesis. ( 10–12 ) We previously reported that rasH2 mice had enhanced chemical skin carcinogenesis in response to treatment with DMBA and TPA. ( 9 ) In rasH2 mice, the number and total volume of papillomas were far greater than those of their wild‐type littermates, presumably because of the increased abundance of initiated cells in rasH2 mice.…”
mentioning
confidence: 99%